Metode MCDA Untuk Pengukuran Tingkat Kesadaran Keamanan Informasi Pada Mahasiswa - Dafid .; Dorie Pandora Kesuma (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
In a higher education institution, it is certainly common for students to carry out various academic and non-academic activities using information technology. Awareness of information security is one of the substantial factors in the utilization of these technologies. With low level of awareness, information security incidents will be arising. This research measures the level of information security awareness of STMIK XYZ students. The purpose of this research is to determine the level of information security awareness of students so that actions can be determined that need to be taken to improve low awareness and maintain what is already good. This research using Multiple Criteria Decision Analysis (MCDA) method. The results showed that information security awareness's level of STMIK XYZ students is